Engagement in Integrative and Nonpharmacologic Pain Management Modalities Among Adults with Chronic Pain: Analysis of the 2019 National Health Interview Survey - Rodgers-Melnick SN; Trager RJ; Love TE; Dusek JA (Journal of Pain Research, 2024)
Samuel N Rodgers-Melnick,1,2 Robert J Trager,1 Thomas E Love,2– 4 Jeffery A Dusek5 1Connor Whole Health, University Hospitals of Cleveland, Cleveland, OH, USA; 2Department of Population and Quantitative Health Sciences, Case Western Reserve University School of Medicine, Cleveland, OH, USA; 3Department of Medicine, Case Western Reserve University School of Medicine, Cleveland, OH, USA; 4Population Health and Equity Research Institute, The MetroHealth System, Cleveland, OH, USA; 5Department of Family Medicine and Community Health, Case Western Reserve University School of Medicine, Cleveland, OH, USACorrespondence: Samuel N Rodgers-Melnick, University Hospitals Connor Whole Health, 11100 Euclid Avenue, Wearn 548A, Cleveland, OH, 44106, USA, Tel +1 216 844 7727, Fax +1 216 201 6220, Email Samuel.RodgersMelnick@UHhospitals.orgObjective: To examine variables associated with engagement in (1) integrative health and medicine (IHM) and (2) nonpharmacologic modalities rather than opioids among United States adults with chronic pain.Methods: Using the 2019 National Health Interview Survey, we examined sociodemographic, pain, and mental health predictors of (1) the sum of IHM modalities (ie, chiropractic care, yoga/Tai Chi, massage, or meditation/guided imagery) used to manage pain and (2) exclusive engagement in nonpharmacologic pain management modalities (ie, IHM, a chronic pain self-management program, support groups, or physical, rehabilitative, occupational, or talk therapy) or opioids in the past 3 months.Results: Metropolitan residency, higher family income, higher education levels, increased number of pain locations, and increased frequency of pain limiting life/work activities were associated with increased odds of IHM engagement. Older age, male sex, non-Hispanic Black/African American race/ethnicity, and daily opioid use were associated with decreased odds of IHM engagement. Older age, male sex, and increased depressive symptoms were associated with decreases in the count of IHM modalities used to manage pain. Metropolitan residency, higher family income, and higher education levels were associated with increased odds of exclusive nonpharmacologic modality engagement. Older age and increasing frequency of pain limiting life/work activities were associated with decreased odds of exclusive nonpharmacologic modality engagement.Conclusions: We identified several contrasts between factors prevalent among individuals with chronic pain and factors associated with engagement in nonpharmacologic and IHM modalities. These results support efforts to address barriers to accessing these modalities among subpopulations of adults with chronic pain (eg, older adults, individuals identifying as Black/African American, rural residents, and those with lower levels of education and income).Plain Language Summary: This study examined factors influencing the use of integrative health and non-drug treatments for chronic pain in the United States. Results revealed that metropolitan residence, higher income, and education were associated with increased use of these treatments, while older age, male sex, daily opioid use, and non-Hispanic Black/African American ethnicity were associated with decreased use. The findings emphasize the importance of addressing barriers to these forms of care, especially among older adults, Black/African American individuals, and those with higher depressive symptoms and lower education and income levels, who are more likely to have chronic pain.Keywords: integrative medicine, chronic pain, nonpharmacologic, opioids